Cell cultures in replacement therapy - E. M. Petruchuk; N. V. Shalunova; Yu. V. Olefir; I. V. Borisevich; V. V. Perekrest; V. A. Shevtsov; A. V. Rukavishnikov; L. M. Khantimirova (Биопрепараты: Профилактика, диагностика, лечение, 2018)
Cell replacement therapy is one of the top priority areas of modern medicine, which is aimed at restoring the structure and functions of damaged tissues by transplanting cells grown in vitro . The article summarizes data obtained in several studies of diploid cell lines (allogeneic fibroblasts) used as replacement therapy in various therapeutic areas as part of application of medical technology innovations. The article describes benefits of using fibroblasts and the routes of cell culture administration. At present the use of medicinal products containing viable human cells (biomedical cell products) is regulated by Federal Law 180-FZ «On biomedical cell products» of 23 June 2016. Cell cultures used in the production of biomedical cell products should be morphologically homogeneous populations of cells derived from a specific tissue and should have a limited life span, a stable karyotype (at least 75 % of cells should have a double set of chromosomes), should not be associated with cancer risks, be free from extraneous agents, have low levels of histocompatibility antigens expression. According to 180-FZ, all characteristics of a cell line supporting the quality of a biomedical cell product should be reflected in the biomedical cell product specification. Before the adoption of 180-FZ only certified cell cultures could be clinically used. The therapeutic potential of fibroblasts related to optimization of reparative processes, improvement of regenerative and adaptive capabilities, as well as the accumulated experience of their clinical use are stirring interest to the development of fibroblast-based biomedical cell products and their use as replacement therapy. However, it should be pointed out that according to 180-FZ biomedical cell products may not be produced using «biological material obtained by interrupting or jeopardising an embryo/fetus development process».